Bad Heritage: The American Viking Fantasy, from the Nineteenth Century to Now - Karl Steel (2014)
Here's a key paragraph: "This chapter will be an exploration of the heritage function of Vikings in America. It will look at their presumptive whiteness, from the early nineteenth century, through the real mania for all things Viking in the mid to late nineteenth century, and on to present day fascinations with the Norse in popular music, neo-Norse religion, and white supremacy. As I will demonstrate, a fantasized whiteness is at the core of much of the American Viking fantasy: Historic Newfoundland is no anomaly. Witness, for example, a recent Newfoundland and Labrador Tourist board television commercial, featuring a set of light-skinned children frolicking amid the reconstructions of turf houses, whose voiceover concludes with “their journey ended [here]…the place your journey will begin” (L’anse Aux Meadows). The Vikings provide a break, starting (Canadian) history, but also ending it, by establishing a bond that collapses the distinction between past to present. My central concern will be with how this fantasized historical bond of whiteness works as heritage both of freedom and as an obligation, a burden, or a duty, as, in short, anything but a freedom. My ultimate goal will be to complicate claims of authenticity and straightforward cultural transmission to make them useless for white supremacist heritage claims, while preserving the possibility for a culturally heterogeneous Viking heritage that might operate outside the strictures of purity. "